Allogeneic hematopoietic cell transplantation for acute myeloid leukemia with BCR::ABL1 fusion - Shohei Mizuno; Akiyoshi Takami; Koji Kawamura; Kaito Harada; Masuko Masayoshi; Shingo Yano; Ayumu Ito; Yukiyasu Ozawa; Fumihiko Ouchi; Takashi Ashida; Yuichiro Nawa; Tatsuo Ichinohe; et al. (eJHaem, 2024)
Abstract BCR::ABL1 fusion is found in < 1% of de novo acute myeloid leukemia (AML) cases and confers a poor prognosis. This Japanese nationwide survey analyzed patients with AML (n = 22) and mixed phenotype acute leukemia (MPAL) (n = 10) with t(9;22) or BCR::ABL1 who underwent allogeneic hematopoietic cell transplantation (allo‐HCT) between 2002 and 2018. The 3‐year overall survival (OS) rates were 81.3% and 56.0%, respectively (p = 0.15), and leukemia‐free survival (LFS) rates were 76.2% and 42.0%, respectively (p = 0.10) in patients with AML and MPAL. The relapse rates were 9.5% and 14.0% (p = 0.93), and the non‐relapse mortality (NRM) rates were 14.3% and 44.0%, respectively (p = 0.10) in patients with AML and MPAL. One in 17 patients with AML, with pre‐transplant tyrosine kinase inhibitors (TKI), and three in five patients with AML, without pre‐transplant TKI, did not achieve complete remission (CR) before allo‐HCT (p = 0.024). Among the 20 patients with known disease status after allo‐HCT, 95.0% were in hematological or molecular CR. None of the four patients who received post‐transplant TKI for prophylaxis or measurable residual disease relapse experienced hematological relapse. In conclusion, our results suggest that pre‐transplant TKI could improve disease status before allo‐HCT. Moreover, allo‐HCT resulted in high OS, high LFS, low relapse, and low NRM rates in patients with AML with BCR::ABL1.